(untitled) (Journal of Asian Development Studies, 2024)
The study aims to investigate the impact of entrepreneurial orientation on small and medium enterprises’ performance. A survey-based quantitative research design was used to collect primary data from registered SMEs. There are 3010 registered small and medium-sized enterprises. A stratified sampling technique was used for calculating sample size, and 353 respondents were selected for data collection with the help of a questionnaire; analysis was performed through descriptive statistics such as frequency, percentages, and regression analysis were performed. The result shows There is a positive impact of risk-taking on small and medium sized enterprises’ performance, a positive impact of innovation on small and medium-sized enterprises’ performance, a positive impact of proactiveness on small and medium-sized enterprises’ performance, a positive impact of autonomy the on small and medium-size enterprises’ performance. The competitive aggressiveness has a positive impact on small and medium-size enterprises’ performance. The study recommended the relationship between entrepreneurial orientation and SME performance is a topic of significant significance and potential for providing clues to the keys to success in this vital economic sector. When we know how entrepreneurial orientation affects SME performance, policy leaders in government and businesses, financial institutions or industry associations, and other stakeholders will be able to devise tailored strategies that promote a favourable environment for the growth and continued existence of Small and Medium-sized Enterprises; Further research can also shed light on some of the actionable advice for SMEs to improve their entrepreneurial capability and competitive advantage.